An Examination of Academic Library Privacy Policy Compliance with Professional Guidelines - Valentine, Greta; Barron, Kate (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2022)
Objective – The tension between upholding privacy as a professional value and the ubiquity of collecting patrons’ data to provide online services is now common in libraries. Privacy policies that explain how the library collects and uses patron records are one way libraries can provide transparency around this issue. This study examines 78 policies collected from the public websites of U.S. Association of Research Libraries’ (ARL) members and examines these policies for compliance with American Library Association (ALA) guidelines on privacy policy content. This overview can provide library policy makers with a sense of trends in the privacy policies of research-intensive academic libraries, and a sense of the gaps where current policies (and guidelines) may not adequately address current privacy concerns.Methods – Content analysis was applied to analyze all privacy policies. A deductive codebook based on ALA privacy policy guidelines was first used to code all policies. The authors used consensus coding to arrive at agreement about where codes were present. An inductive codebook was then developed to address themes present in the text that remained uncoded after initial deductive coding.Results – Deductive coding indicated low policy compliance with ALA guidelines. None of the 78 policies contained all 20 codes derived from the guidelines, and only 6% contained more than half. No individual policy contained more than 75% of the content recommended by ALA. Inductive coding revealed themes that expanded on the ALA guidelines or addressed emerging privacy concerns such as library-initiated data collection and sharing patron data with institutional partners. No single inductive code appeared in more than 63% of policies.Conclusion – Academic library privacy policies appear to be evolving to address emerging concerns such as library-initiated data collection, invisible data collection via vendor platforms, and data sharing with institutional partners. However, this study indicates that most libraries do not provide patrons with a policy that comprehensively addresses how patrons’ data are obtained, used, and shared by the library.